The Personality Dynamics of the Main Characters in the Novel Kereta Semar Lembu: A Psychoanalytic Study by Sigmund Freud - Novi Imroatul Awaliyah; Moh. Ahsan Shohifur Rizal (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to examine the personality dynamics of the main character in the novel through Sigmund Freud’s psychoanalysis. The research focuses on the structure of the main character’s personality and how the interaction between these elements gives rise to personality dynamics in the form of instincts (life and death) and anxiety (realistic, neurotic, and moral). Using a descriptive qualitative approach, this study analyzes the narrative text and dialogue in the novel Kereta Semar Lembu through reading and note-taking techniques and content analysis techniques. The results show that the main character has a dominant id, driving the fulfillment of the pleasure principle and sexual needs. The ego mediates between the id and social reality and the demands of the superego through rational decisions and acceptance of consequences. The superego represents moral values by bringing up social and moral norms, guilt due to moral violations, and anxiety due to moral inconsistencies. The interaction of these three aspects forms the dynamics of personality, namely the instinct to live, which is seen through the desire for exploration and self-growth, as well as adaptation to reality. The death instinct manifests itself in destructive impulses and the desire to end one’s life. Realistic anxiety is evident in the fear of facing reality and damnation, while moral anxiety is reflected in feelings of guilt, sinfulness, and fear of social and religious punishment. These findings confirm that childhood experiences and social environment greatly contribute to shaping the main character’s personality.